Pengaruh Sedimentasi Terhadap Debit Saluran Sekunder Parota Pada Jaringan Irigasi Sanrego Kabupaten Bone - Alam, Syamsu; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Sediment contained in the channel changes dimensions and can indirectly cause less optimum water flow. Sedimentation buildup in different waterways, field measurements were taken to determine the measured sediment volume and the capacity change in the Bpr.5-Bpr6 secondary channel caused by the influence of sediment. Data collection in the field was carried out in the parota secondary irrigation canal, which is located in the village of Sanrego, Kahu sub-district, Bone district. The data sources in this study are primary data obtained directly from field measurements and secondary data obtained from the literature. The volume of sedimentation in the secondary canal in the Sanrego irrigation network, Bone Regency is Bpr.5-Bpr6 is 707,903 m3, while the capacity of the secondary canal from the initial dimension of the canal with a cross-sectional area is 5.01 m2. After sedimentation, the cross-sectional area becomes 3,985 m2. with the initial discharge of the channel is 2.96 m3/sec. after sedimentation occurs, the channel discharge becomes 2.19 m3/sec.